2009
DOI: 10.1111/j.1600-0404.1998.tb00642.x
|View full text |Cite
|
Sign up to set email alerts
|

The anterior inferior cerebellar artery infarcts: a clinical-magnetic resonance imaging study

Abstract: Acute infarcts of the anterior inferior cerebellar artery (AICA) are unusual. We report 15 cases of AICA infarcts and their correlation with the topography of the lesion by brain MRI. During 2 years we prospectively identified 7 cases of AICA infarcts among 770 acute strokes (0.9% of the acute strokes seen in our department). We studied these cases and also another 8 that we found retrospectively. Most patients (8/15) had a unilateral affeétation of both middle cerebellar peduncle (MCP) and inferior lateral po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 11 publications
0
28
0
2
Order By: Relevance
“…Clinical pictures vary according to the infarction localization in the infarctions compatible with AICA irrigation area. Whereas symptoms such as isolated vertigo mimicking labyrinthitis or ataxia are present in partial AICA, bilateral AICA may follow a severe clinical course which ultimately can cause coma ( 6,7,8). In our case, although bilateral involvement was present, it was not that severe.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Clinical pictures vary according to the infarction localization in the infarctions compatible with AICA irrigation area. Whereas symptoms such as isolated vertigo mimicking labyrinthitis or ataxia are present in partial AICA, bilateral AICA may follow a severe clinical course which ultimately can cause coma ( 6,7,8). In our case, although bilateral involvement was present, it was not that severe.…”
Section: Discussionmentioning
confidence: 56%
“…Only six cases were reported in a study which documented 1350 cases with posterior system infarction (5). In another study it was reported that AICA formed 0.9% of all the cerebrovascular events and 5.2% of vertebrobasillar infarctions (6). Bilateral AICA infarctions are present only in the form of case reports in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The structures mainly damaged in these scenarios are the middle cerebellar peduncle and flocculus, with extension into the neighboring cerebellar lobules between the territories of the SCA and PICA. Roquer et al in 1998 54 presented a correlative study between neurological symptoms and findings on MRI in patients with AICA strokes using the anatomical diagrams of Amarenco and Hauw. 2 The middle cerebellar peduncle was the core of the affected territory in AICA strokes and was suggested as the radiological hallmark of this vascular insult.…”
Section: Cerebellar and Brainstem Infarctsmentioning
confidence: 99%
“…İpsilateral fasial parezi, işitme kaybı, trigeminal alanda duyu kusuru, Horner sendromu, ipsilateral serebellar bulgu ve kontralateral ekstremite ve gövd-ede ağrı, ısı duyusunda azalma da bu bulgulara eşlik edebilir (2, 5). AICA infarktları ile ilgili literatür incelendiğinde; hastaların nörootolojik bulguları değerlendirilmeden beyin ve serebellar bulguları ile tanımlanan olgular da mevcuttur (6,7,8). İşitme kaybı, AICA infarktı gelişen hastalarda sık rastlanan bir bulgudur.…”
unclassified
“…Ancak, görülme sıklığı yüzde % 30-100 arasında değişmektedir (9). Roguer ve arkadaşları AICA infarktı saptanan 15 hastanın 6'sında (3), Ameranco ise 13 hastanın 3'ünde işitme kaybı saptamışlardır (8). Olguların bazılarında ani gelişen işitme kaybı tanımlanmıştır (5, 10, 11).…”
unclassified